The Rights of Children from Unregistered Marriages: Between Certainty and the Practice of Protection - Pantui, Darwin; Kasim, Nur Mohamad; Dungga, Weny Almoravid (Hang Tuah Law Journal, 2025)
This study aims to analyze efforts to fulfill children's rights a decade after the Constitutional Court Decision No. 46/PUU-VIII/2010, focusing on the practice of protecting the rights of children born from unregistered marriages, reflecting legal certainty. The methodology used in this research is normative research with a legislative approach and case approach, utilizing primary and secondary legal materials as the main sources of analysis. The results show that Constitutional Court Decision No. 46/PUU-VIII/2010 provides a crucial legal foundation in guaranteeing the rights of children born from unregistered marriages, creating clearer recognition and legal status for these children. Furthermore, the decision opened the possibility for children born from unregistered marriages to request a legal determination through the court system under the Supreme Court's jurisdiction. This study also highlights the alignment between the Constitutional Court Decision and the establishment of other judicial bodies, emphasizing the importance of legal certainty for children born from unregistered marriages, ensuring that they can live, grow, and develop with legally recognized rights.